Computer and analytical calculations for optimization of cycle separation of ash - Ryzhov, Volodymyr (Technology audit and production reserves, 2019)
The object of research is the efficiency of cleaning of flue gases in group cyclones of CN-15 type with a diameter of 0.7 m steam boiler KE10-14-285 when burning sunflower husk at an oil and fat plant. One of the biggest problems of different sunflower husk combustion technologies in boiler units at oil and fat plants is the low efficiency of trapping in typical cyclones of sunflower husk ash due to the considerable dispersion of ash and other factors. The estimation was made by the use of the developed analytical models and computer technology CFD – Computational Fluid Dynamic of the Certified SolidWorks-2009 computer program on the settlement complex (KPI). The calculated and experimental data on the estimation of the efficiency of flue gas cleaning in cyclones of the steam boiler «KE 10-14-285» (Ukraine) during the combustion of sunflower husk at the Vinnytsia Oil and Fat Plant (Ukraine) is given. The possibility of significant reduction of ash removal into the air during reconstruction according to of new technology of group cyclones type CN-15 (Ukraine) is shown. Using computer and analytical calculations, the possibility of increasing the overall efficiency of flue gas cleaning from ash during combustion in boilers of dream husk is substantiated to 90 % instead of 45…55 %. In the course of the study, the technology of creating high-intensity cyclone cyclones at flow stage with flow of various turbulizers was used at the stepped inlet section. Thanks to this technology, it is possible to reduce the ash removal from cyclone by more than three times compared to similar indicators in typical cyclones prior to their modernization. This makes it possible to satisfy the sanitary standards of the European Union and Ukraine with minimal capital expenditure. This result is achieved due to a number of features – in particular, a sharp increase in the ripple component of the flow rate.